A REVIEW ON HYBRID MULTIPLIER AND FUNCTIONALITY - Rani, Mamta (Innovative Research Thoughts, 2018)
This paper discusses the digital system along with its basic functionality. In this paper the discussion has been made on existing researches related to Modified Booth Multipliers With a expected Fractional Product Array, Multiplier Reduction Tree with Logarithmic Logic Depth and Regular connectivity, Multiplication Acceleration Through Twin Precision Magnus, Implementation of a High speed Multiplication on SOC using Twin precision process. The multiplier and their working have been discussed in this paper.